Comparison of Effect of Prone and Right Lateral Positions on Gastric Residual Volume in Preterm Newborns - Mahbobeh Sajadi; Mehran Akbari; Saeed Alinejad; Sharareh Khosravi (Mashhad University of Medical Sciences, 2019)
Background: Nutritional problems in premature newborns are of great importance for their development. In this regard, the neonatal positioning during and after feeding can have a significant effect on their nutritional tolerance. Therefore, the present study was conducted to compare the effect of two positions (i.e., prone and right lateral) on gastric residual volume in preterm newborns after gavage feeding. Methods: This crossover clinical trial was performed on 52 eligible premature newborns who were selected using purposive sampling. They were randomly assigned into two groups, namely A and B. After gavage feeding, the newborns in group A were placed in the prone position and their gastric residual volume was measured 3 times. Subsequently, after gavage feeding, they were put in the right lateral position and subjected to the same measurement. On the other hand, the newborns in group B were first put in the right lateral and then a prone position. The other procedures and measurements were performed the same as those in group A. The data were analyzed using repeated measure ANOVA. Results: The results indicated a significant difference regarding the mean value of gastric residual volume (P=0.001). Moreover, the mean gastric residual volume in the prone position (2.152±0.299) was significantly (P=0.001) lower than that in the lateral position (2.618±0.403). Conclusion: According to the results, The prone position can reduce the mean gastric residual. Therefore, it can be recommended as a suitable position after gavage feeding in premature newborns.